A Urinary Bcl-2 Surface Acoustic Wave Biosensor for Early Ovarian Cancer Detection - ŞİŞMAN, ALPER (MDPI AG, 2012)
In this study, the design, fabrication, surface functionalization and experimental characterization of an ultrasonic MEMS biosensor for urinary anti-apoptotic protein B-cell lymphoma 2 (Bcl-2) detection with sub ng/mL sensitivity is presented. It was previously shown that urinary Bcl-2 levels are reliably elevated during early and late stages of ovarian cancer. Our biosensor uses shear horizontal (SH) surface acoustic waves (SAWs) on surface functionalized ST-cut Quartz to quantify the mass loading change by protein adhesion to the delay path. SH-SAWs were generated and received by a pair of micro-fabricated interdigital transducers (IDTs) separated by a judiciously designed delay path. The delay path was surface-functionalized with monoclonal antibodies, ODMS, Protein A/G and Pluronic F127 for optimal Bcl-2 capture with minimal non-specific adsorption. Bcl-2 concentrations were quantified by the resulting resonance frequency shift detected by a custom designed resonator circuit. The target sensitivity for diagnosis and identifying the stage of ovarian cancer was successfully achieved with demonstrated Bcl-2 detection capability of 500 pg/mL. It was also shown that resonance frequency shift increases linearly with increasing Bcl-2 concentration.
Keywords: ovarian cancer; MEMS; piezoelectric; sensor; early detection; Bcl-2; SH; SAW; SAM; ultrasound; ESCHERICHIA-COLI; PROPAGATION; BIOMARKERS; DISCOVERY; EFFICACY; SENSORS; BIOLOGY; LINBO3; WOMEN; STAGE